2019
DOI: 10.4055/cios.2019.11.1.15
|View full text |Cite
|
Sign up to set email alerts
|

Difference in Mortality Rate by Type of Anticoagulant in Elderly Patients with Cardiovascular Disease after Hip Fractures

Abstract: Background The purpose of this study was to investigate the difference in mortalilty rate between cardiovascular disease (CVD) patients and non-CVD patients after hip fracture surgery performed in elderly patients. In addition, we compared the effect of CVD medication on mortality after hip fracture surgery. Methods Patients who underwent surgery for femoral intertrochanteric or neck fracture from January 2003 to December 2013 were enrolled in this study. After applying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…In accordance to our ndings Cha et al in 2018 also found that even thrombocyte aggregation inhibitors, such as aspirin, were associated with more packed cell supplementation. (16) This is possible due to the duration of the effect of thrombocyte aggregation inhibitors, which last during the entire lifespan of the platelets, which is usually 5 to 9 days. (17) Since prolonged hospital stay is associated with complications such as pneumonias and decubital ulcers, a stay as short as possible is desirable for these fragile patients.…”
Section: Discussionmentioning
confidence: 99%
“…In accordance to our ndings Cha et al in 2018 also found that even thrombocyte aggregation inhibitors, such as aspirin, were associated with more packed cell supplementation. (16) This is possible due to the duration of the effect of thrombocyte aggregation inhibitors, which last during the entire lifespan of the platelets, which is usually 5 to 9 days. (17) Since prolonged hospital stay is associated with complications such as pneumonias and decubital ulcers, a stay as short as possible is desirable for these fragile patients.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 30-50% of patients with hip fractures have cardiovascular comorbidity that requires antithrombotic treatment (antiplatelet, vitamin K antagonists (VKA) or direct oral anticoagulants (DOACs) [126]. Early surgery (within 48 h) has been proven to reduce complications and mortality at 30 days and 1 year in hip fracture patients even if receiving antithrombotic treatment [127][128][129], although these drugs can potentially interfere with regional anaesthesia or increase perioperative bleeding. Choosing the optimal moment for surgery should thus balance thrombotic and bleeding risks with the risks of delayed surgery and the benefits and risks of spinal anaesthesia.…”
Section: Perioperative Antithrombotic Managementmentioning
confidence: 99%
“…2 Stable intertrochanteric fractures 3 can be managed with osteosynthesis with consistent successful outcomes, while unstable intertrochanteric fractures (UIF) are more difficult to handle due to the difficulties of achieving anatomical reduction and related comorbid conditions that raise the risk of morbidity and mortality 4,5 In the elderly, an hip fractures are associated with a 20% mortality rate. 6 Intertrochanteric femur fractures account for 50% of all hip fractures resulting from a low-energy mechanism, like a fall from standing height. Attempts to repair these fractures sometimes result in excessive collapse, poor bone quality, loss of fixation, and latency screw cut-out.…”
Section: Introductionmentioning
confidence: 99%